Stabilitas Hasil Galur-galur Harapan Padi Sawah - Abdullah, Buang; Safitri, Heni (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2014)
The yield stability of genotype needs to be known before a genotype is released as new variety. The objective of this research was to identify yield and yield stability of rice breeding lines. Multilocational yield trials (MYTs) were conducted at nine locations in the 2009 dry and wet seasons. Ten promising lines were evaluated along with two control varieties, arranged in a randomized complete block design (RCBD) with four replications. The result showed that five lines, i.e. B11007E-MR-3-2-PN-1-2, B10542FKN-90-1, B10533F-KN-12-2, B10543E-PN-17-1, and B10541F-KN-31-3 were considered as stable in all environments. The yield of four stable lines, i.e. B11007E-MR-3-2-PN-1-2, B10542F-KN-90-1, B10533F-KN-12-2, and B10541F-KN-31-3 each was not significantly different from Ciherang. The yield of glutinous rice line B10543E-PN-17-1 also was not significantly different from Ciasem. The yield stability and the agronomic appearance of these two lines were the same or better than those of Ciherang or Ciasem.